Implementasi Algoritma Approximate String Matching Pada Aplikasi Pengarsipan Dokumen Ekspor Barang - Sihotang, Yola Annisa (Management of Information System Journal, 2023)
This thesis proposal has the title "Implementation of the Approximate String Matching Algorithm in the Export Goods Document Archiving Application (Case Study: PT. Chitra Kalpika Mas Kab. Deli Serdang". This proposal was made based on observations made at PT. Chitra Kalpika Mas by looking at the filing system export documents which are still done manually, the author created a new system design to improve the old system. The problem studied in this research is how to search export document archives and the obstacles faced by PT. Chitra Kalpika Mas. And what obstacles have been taken to overcome existing obstacles. Therefore, an application program is needed that can help employees to complete their tasks more easily, one of which is carrying out the process of searching for export document archive data. Based on the research results, it can be concluded that searching for export document archives at PT. Chitra Kalpika Mas is still done manually. Therefore, it is necessary to design a new application using a computer program according to the needs of office employees so that use is easier to obtain quickly and accurately. With the design of the export document archive application, it can make it easier to process reports, add, change and delete data and can provide information whenever needed.